Für eine Feministische Politische Ökologie des Klimawandels: Überlegungen zu einer erweiterten Analyseperspektive auf Geschlecht und Anpassung - Hackfort, Sarah (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2014)
Social science climate research falls significantly short of the reflective power of feminist thought when it comes to the role of gender and its intersection with other categories of social difference and hierarchy in adaptation to climate change. This article seeks to narrow this gap by broadening the perspectives for an analysis of gender and adaptation to climate change from an intersectional and Political Ecology perspective. It argues for an multi-level framework that considers and relates three analytical levels: the political economic mechanisms of hierarchization, which shape the individual and collective scope of action through their material gender-, and class- or age specific effects, the effects of hegemonic representations and discourses, and the subject level in order to capture the identity political dynamics that contribute to unequal options for climate adaptation among subjects. It provides empirical illustrations from a case study in Mexico/Chiapas.